Anthropometric changes caused by hepatitis C treatment with interferon and ribavirin: which patients and which measures are affected? - Araújo, L. F. [UNESP]; Dorna, M. S. [UNESP]; Santos, L. A.A. [UNESP]; Lima, T. B. [UNESP]; Ietsugu, M. V. [UNESP]; Nunes, H. R.C. [UNESP]; Paiva, S. A.R. [UNESP]; Silva, G. F. [UNESP]; Qi, X. [UNESP]; Romeiro, F. G. [UNESP] (Springer Nature, 2017)
Background: Chronic hepatitis C causes chronic hepatic inflammation, which can lead to cirrhosis, terminal liver failure, and hepatocellular carcinoma. The treatment aims to achieve viral clearance, but the usage of pegylated interferon and ribavirin is linked to side effects such as severe weight loss, which can lead to complications and treatment discontinuation. The aim of this study was to investigate which anthropometric measures were more affected in patients with chronic hepatitis C during 24 weeks of treatment with pegylated interferon and ribavirin. Then, the influence of age, sex, hepatic fibrosis stage, and ribavirin doses on each measure was also evaluated. Methods: Seventy-six patients were included and their weight, triceps skin fold thickness, arm circumference, middle-arm muscle circumference, and corrected arm muscle area were measured before and after 24 weeks of treatment. Epidemiological data and liver biopsy findings were obtained from patients’ records. The sample was divided into two groups: one with advanced hepatic fibrosis and another group with mild to moderate fibrosis. Comparisons into each group were made using Wilcoxon or paired t tests. After that, a linear regression model was applied to estimate the anthropometric changes during the treatment according to age, sex, hepatic fibrosis stage, and ribavirin doses. Results: The subjects suffered reductions of important anthropometric measures, mainly related to fat mass (p < 0.001). Some decrease of fat-free mass was also observed in subjects with advanced fibrosis. The statistic model showed that age and sex were more associated with the anthropometric changes observed. Conclusions: In conclusion, the antiviral treatment caused loss of relevant anthropometric measures, and the model proposed was able to estimate some of them.
Keywords: Anthropometry; Hepatitis C; Linear regression; Liver fibrosis; Weight loss